Analyzing the distribution of researchers in China: An approach using multiscale geographically weighted regression. (26th November 2020) - Gu, Hengyu; Yu, Hanchen; Sachdeva, Mehak; Liu, Ye
Abstract: We employ a Multiscale Geographically Weighted Regression (MGWR) model to examine the spatial variation of researchers in China in 2015 and its determinants. It is found that the distribution of researchers is driven by the economy in urban centers, public services, natural areas of recreation, urban consumption, and work‐related facilities. Results from the MGWR model conclusively identify significant spatial non‐stationarity in the determinants measuring scientific researchers' distribution. Other factors such as per capita GDP, the number of hospital beds per 10, 000 inhabitants, and public financial expenditures influence the distribution of researchers more in the Western cities, and their effect decreases steadily from West to East. Air pollutants affect researchers negatively in the eastern part of the country, while the percentage of available green land is a strong driver in the central and western parts. The factor measuring the effect of the number of universities is seen to affect researchers more strongly in the northwestern and northeastern cities. Other findings further suggest that the economy and public services in cities have a consistent effect on the distribution of researchers across the country whereas, natural areas of recreation, work‐related facilities, and urban consumption have a significantly varying effect across cities.